Application of enhanced recovery after surgery in total knee arthroplasty in patients with haemophilia A: A pilot study. Issue 1 (28th August 2020) - Wu, Yan; Xue, Haipeng; Zhang, Wenqiang; Wu, Yuhong; Yang, Yanwei; Ji, Hong
Abstract: Aim: To identify the effect of enhanced recovery after surgery (ERAS) and rapid rehabilitation concepts on the outcomes of patients with haemophilia A undergoing total knee arthroplasty. Design: Randomized controlled trial. Methods: The primary endpoint was postoperative hospital stay. The secondary endpoints were pain scores, joint function scores, haemoglobin levels at 3 and 7 days after surgery and satisfaction with hospitalization. Results: Thirty‐two patients were enrolled. Compared with the routine nursing group, the ERAS group showed shorter postoperative hospital stay (14.2 SD 0.8 vs. 16.6 ± 1.3 days, p  < .001), smaller amounts of blood transfusion (924 SD 317 vs. 1, 263 SD 449 ml, p  = .020) and coagulation factors (37, 325 SD 5, 996 vs. 48, 475 SD 8, 019 U, p  < .001), lower pain scores at 3 (3.3 SD 0.7 vs. 4.3 SD 0.7, p  = .002) and 7 (2.3 SD 0.7 vs. 2.8 ± 0.5, p  = .015) days, lower hospital for special surgery knee scores at 3 (59.9 SD 7.8 vs. 53.6 SD 5.9, p  = .016) and 7 (77.9 SD 6.9 vs. 71.1 ± 7.1, p  = .009) days and higher satisfaction with hospitalization (94.3 SD 1.4 vs. 92.7 SD 1.6, p  = .004).